(untitled) (Confluenţe Bibliologice, 2013)
The article presents the experience in creating authority ﬁles in the USARB Scientiﬁc Library, process started with the implementation of integrated library software TinLib. The stages of development are presented, the sources used to construct the concept of authority ﬁle, route - mape, the responsibilities, the questionnaire, form of ﬁelds, sample ﬁles of authority names of people (teachers, librarians) in the TinLib and webOPAC. Also, the diﬃculties are presented in creating the authority ﬁles, as well as some proposals for settlement and improvement.